SEPSIS PATHOGENS AND ANTIBIOTIC RESISTANCE IN THONG NHAT HOSPITAL - Ngọc Lân, Nguyễn; Thanh Liêm, Nguyễn; Tài Lộc, Trần; Thị Thanh Tâm, Nguyễn; Thị Thanh Tâm, Phan (Journal of Health and Aging, 2025)
This study investigates the distribution of pathogenic microorganisms and their antibiotic resistance status in bloodstream infections at Thong Nhat Hospital from April 30, 2024, to May 1, 2025. Retrospective, cross-sectional descriptive study conducted on 770 microbial isolates obtained from blood samples from April 30, 2024, to May 1, 2025, at Thong Nhat Hospital. Among the total 770 isolated strains, bacteria accounted for 97.27%, and fungi accounted for 2.73%. The common pathogens included Coagulase-negative Staphylococci (30.44%), Escherichia coli (21.23%), Staphylococcus aureus (8.54%), Klebsiella pneumoniae (7.34%), and Pseudomonas aeruginosa (2.94%). E. coli showed >80% susceptibility to amikacin and piperacillin/tazobactam and >97% susceptibility to carbapenems. K. pneumoniae demonstrated resistance rates of 30.2% to imipenem, 31,3% to meropenem, and 25.5% to ertapenem. P. aeruginosa resistance rates were 50% to imipenem and 40.9% to meropenem. S. aureus exhibited high resistance to benzylpenicillin (96.6%), erythromycin (75.9%), and clindamycin (67.2%) but remained 100% susceptible to vancomycin, linezolid, teicoplanin, and tigecycline. The MRSA rate was 62.5%. Candida spp. remained susceptible to commonly used antifungal agents. Bacteria are the primary cause of bloodstream infections. Multidrug-resistant strains such as P. aeruginosa, K. pneumoniae, and MRSA account for a significant proportion. Continuous monitoring of resistance patterns supports clinicians in selecting appropriate antibiotics, thereby reducing mortality and treatment costs.
Keywords: bloodstream infection; antibiotic resistance; Thong Nhat Hospital